2016
DOI: 10.17511/ijphr.2016.i2.04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression amongst adolescents in rural area of South India – a school based cross sectional study

Abstract: Introduction:Depression is common in adolescents and especially in high school students and is one of the most frequent mental disorders among teenagers. Depression in adolescents is an under recognized mental health problem because they remain indecisive to disclose their feelings and seldom seek psychiatric help. One of the factors that make depression so difficult to diagnose in adolescents is the common behavioural changes that are normally associated with the hormonal changes of this period. It has only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
(5 reference statements)
1
9
0
Order By: Relevance
“…Mild depression was prevalent among 29.7% participants from Chandigarh, 15.5% moderate, 3.7% moderately severe depression A relatively higher prevalence of 49% was reported by a school based study done among 248 adolescents in a rural area near Mangalore, Karnataka, using the PHQ-9; where 67.6% had mild depression, 23% moderate, 8.6% moderately severe and 0.8% had severe depression [9]. These studies among school-going adolescents point out the fact that across the country, adolescents are experiencing unacceptably high rates of depression.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Mild depression was prevalent among 29.7% participants from Chandigarh, 15.5% moderate, 3.7% moderately severe depression A relatively higher prevalence of 49% was reported by a school based study done among 248 adolescents in a rural area near Mangalore, Karnataka, using the PHQ-9; where 67.6% had mild depression, 23% moderate, 8.6% moderately severe and 0.8% had severe depression [9]. These studies among school-going adolescents point out the fact that across the country, adolescents are experiencing unacceptably high rates of depression.…”
Section: Discussionmentioning
confidence: 85%
“…There were two government schools and one government-aided school, and these three schools were included in the study. Based on a previous study [9], where the prevalence of depression among rural adolescents was found to be 49%, with an absolute precision of 10%, 95% confidence limits and a non-response rate of 30%, the sample size was determined to be 125. However, on request from the school authorities, we invited all adolescents enrolled in the three schools to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] from Chennai, south India (60.8%, mild 37.1%, moderate 19.4%, severe 4.3%); Chakraborty et al . [ 21 ] from Mangaluru, south India (49%); Urmila et al . [ 22 ] from Pariyaram, Kerala, south India (57.7%); Kumar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from south India, viz. Chennai[ 20 ] and Mangaluru,[ 21 ] noted that depression among adolescents increases with age. However, Jayashree et al .…”
Section: Discussionmentioning
confidence: 99%